A Soft Grip: Magnesium Complexes with a Phosphine‐Modified Phosphonium Diylidic Lewis Base. Issue 48 (24th October 2016) - Langer, Jens; Kosygin, Irina; Puchta, Ralph; Pahl, Jürgen; Harder, Sjoerd
Abstract: Simple strategies to obtain magnesium complexes with the soft chelating diylidic ligand [Ph2 PCHPPh2 (fluorenylidene)] − (dppmflu − ) were developed to evaluate the influence of the hard acid (cation) and soft base (anion) mismatch on the stability and reactivity of the formed derivatives. Deprotonation of the precursor Ph2 PCH2 PPh2 (flu) (dppmfluH) by an alkylmagnesium derivative or magnesium amide provided access to [Mg(dppmflu)(μ ‐n Bu)2 ], [Mg(dppmflu)N(SiMe3 )2 ], and [Mg(dppmflu)(μ ‐ Me)2 ], which were used as starting materials for further investigations. The reaction of [Mg(dppmflu)(μ ‐n Bu)2 ] with PhSiH3 in the presence of THF allowed isolation of the magnesium hydride complex [Mg(dppmflu)(μ ‐ H)(thf)2 ] without a stabilizing nitrogen donor ligand. Prolonged heating enforced ligand redistribution and [Mg(dppmflu)(μ ‐ H)(thf)2 ] was converted to [Mg(dppmflu)2 ] and MgH2 . The homoleptic derivative [Mg(dppmflu)2 ], in which the magnesium center is in a very soft ligand environment, can open a THF molecule by frustrated Lewis pair reactivity to give [Mg(dppmflu)(μ ‐ OC4 H8 dppmflu)2 ]. Abstract : Soft, but not powerless ! Although considered a hard acid/soft base mismatch, complexes with the diylidic ligand dppmflu − show similar structures and reactivity to their nacnac‐ligated counterparts, with some distinct exceptions (see figure). Stabilized magnesium hydride derivatives and frustrated Lewis pair type reactivity of some of the complexes are reported.